FOSTERING DIGITAL LEGAL AWARENESS IN TEENAGERS: CYBER LAW EDUCATION PROGRAM AT SMAK IMMANUEL BATAM - Padrisan Jamba; Timbul Dompak; Angel Purwanti; Angeline Wong; Remember To Harefa; Erwin Harefa (PUAN INDONESIA, 2026)
This community service initiative addresses the pressing need for comprehensive digital capacity-building among adolescent student leaders through an integrated training program at SMAK Immanuel Batam. Extending beyond simple legal lectures, this 5-week course offers a multidisciplinary approach built on three main pillars: Digital Legal Literacy (Cyber Law), Structural Leadership Communication, and Practical Digital Archiving with Google Sites. Its goal is to enable Grade XI and XII Student Council (OSIS) representatives to confidently navigate digital organizational environments responsibly and avoid legal issues under Law Number 1 of 2024 (The Amended ITE Law). Conducted over five sessions, the program used interactive lectures, real-world cybercrime case studies, and hands-on activities where students created digital archive repositories. The initiative led to a noticeable change in attitude, greatly enhancing students' understanding of data privacy and digital law boundaries. Feedback showed the program’s immediate practical benefits, with participants gaining proficiency in managing cloud documents systematically. Despite challenges like limited legal knowledge among youth, the program's results indicate a positive trend towards developing law-abiding, digitally skilled student leaders. It is recommended that schools embed this comprehensive model into their annual leadership curricula.